Technical assessment of a micro-cogeneration system based on polymer electrolyte membrane fuel cell and fluidized bed autothermal reformer. (15th January 2016) - Di Marcoberardino, Gioele; Roses, Leonardo; Manzolini, Giampaolo
Highlights: Performances of an ATR membrane reactor within a PEM FC micro-CHP system of 5 kWel. Analysis of two different options for the H2 permeate side: sweep and vacuum pump. Optimization of operating conditions in terms of efficiency and membrane area. Distribution of power and thermal consumptions and losses were discussed in detail. A sensitivity analysis highlights the relevant design parameters of the CHP system. Abstract: This work investigates the integration of an autothermal membrane reformer within a micro-CHP system of 5 kWel based on PEM fuel cell. The system modeled is based on a prototype developed within Reforcell European project. The optimization of the micro-CHP system is performed from a thermodynamic point of view aiming at the target of 40% of net electric efficiency and 90% of total system efficiency comparing different configuration and operating conditions. In particular, two hydrogen permeate side options as vacuum or sweep steam are evaluated together with different combination of feed temperature and pressures. A good compromise between electric efficiency (40%) and membrane surface area (0.3 m 2 ) was obtained for the sweep gas case at reaction side conditions of 8 bar, 600 °C and S/C of 2.5. Higher electric efficiency (40.5%) could be achieved by increasing the membrane surface area. The adoption of a vacuum pump simplifies the reactor design and manufacturing, but reduces the net electric efficiency by about 2% points with a membrane surface area of 0.15 m 2 . Finally, the sensitivity analysis highlighted the influence of the main parameters and the design criteria for the definition of the CHP system.